Assessment of the phosphorus dynamics in the wet and dry periods of tropical semiarid reservoirs - Rocha, Maria de Jesus Delmiro (2022)
This dissertation presents an evaluation of the dynamics of total phosphorus (PT) in strategic semi-arid reservoirs, from the watershed scale to the reservoir. The production and arrival of phosphorus from the basin to these water bodies, depending on the climatic period, and the understanding of the causes for the release and resuspension of phosphorus from the sediment of the reservoirs were evaluated. The objective of the first evaluation was to develop a new methodology to estimate the total phosphorus load that reaches the reservoirs in the wet and dry periods and to find evidence of internal load production. The objective of the second evaluation was to describe the importance of point and diffuse sources of pollution, quantify the phosphorus load produced in the watershed, obtain the average load inflowing to the reservoirs and develop flow-concentration relationships of total phosphorus for entering the reservoirs. The third evaluation focused on the production of internal phosphorus load in the reservoir. Gross daily fluxes and net seasonal average release rates were estimated to improve understanding of phosphorus release from sediment. Important results obtained in this dissertation are related to i) the adaptation of classical mass balance models to estimate the production of phosphorus load impacting semi-arid reservoirs, regardless of the period of the year, ii) the detailing of the behavior of the phosphorus flow-concentration relationship depending on the land use of the basin, iii) the combination of methods to assess and quantify rates of phosphorus release from the sediment and iv) the proposition of models and new indicators to estimate the phosphorus load. The results of this work are innovative, since the quantification of the external and internal loads of phosphorus was approximated by the estimation of the loads produced during the wet and dry periods, respectively. Furthermore, this study not only advanced the knowledge of phosphorus dynamics in tropical semi-arid reservoirs, but also provided evidence of the production of significant internal loads in these ecosystems. It is expected that the simple methodologies presented in this dissertation will help in understanding the issues related to total phosphorus in arid/semi-arid regions and help in actions of integrated management of water quality in strategic reservoirs of human supply.